A simple duty cycle control technique to minimize torque ripple in open-end winding induction motor - Muhammad Zaid Aihsan; Auzani Jidin; Azrita Alias; Tole Sutikno (Institute of Advanced Engineering and Science, 2023)
Modern electric vehicles (EVs) that drive an induction motor (IM) fed by a traction inverter are fast gaining popularity due to their simple configuration and robustness. The direct torque control (DTC) technique is one of the best control methods to drive the IM, especially in open-end winding configurations, as it offers more voltage vectors. However, the existence of hysteresis controllers and improper switching technique causes larger torque ripples that leads to variable switching frequency. The study will be focused on the open-end winding induction motor where the direct current (DC) power is fed from both sides of the stator windings using the dual inverter configuration. To minimize the torque ripples, a simple switching technique using the duty cycle control method is proposed by injecting a high-frequency square wave into the default inverter switching status to form the new pattern of voltage vectors. The effectiveness of the proposed technique is tested through MATLAB/Simulink software and validated experimentally with a lab-scale setup using a dSPACE controller. The findings show that the proposed method reduces torque ripple by over 50% while keeping the DTC's simple structure.